The reflection of integrated marketing communications on activating marketing performance: An applied research in the general company for dairy products (Entrepreneurship Journal for Finance and Business, 2022)
Marketing performance is critical in measuring the efficiency of the organization and its ability to achieve its goals of profits, market share and many other goals.  Promotional methods are used in an integrated manner to achieve the maximum impact on the customer, and the research problem was represented by the weak use of marketing communications with which to achieve the market share that corresponds to the quality and efficiency it offers in production.  Research with a first main hypothesis, from which four sub-hypotheses were branched, and a second main hypothesis from which four sub-hypotheses were branched.  The sample of the research was (50) individuals from the directors of departments, divisions, marketing units and marketing workers, and a set of statistical methods used in scientific research were used (arithmetic mean, standard deviation, coefficient of variation, and Spearman correlation coefficient).  The results of the research revealed the existence of a correlation and impact relationship between integrated marketing communications and marketing performance